Squares: a network of places - Rader, Julianne (Kansas State University, 2009)
Over the past centuries, modernization and industrialization has resulted in increasingly disconnected communities. With the advent and increased availability of the personal vehicle, the desire for larger homes on larger lots, and a steady increase in population, cities are all-too-often relinquishing their open and community-oriented spaces to concrete and mortar. Gone are the medieval days in which cities and towns were centered on large community spaces - places where residents could gather, work, shop, and play together. Therefore, this Master’s Project and Report proposes the reintroduction of the town square – the quintessentially European notion of a central city space – as a means to unify modern American cities. To support this proposal, existing research regarding the various characteristics and qualities of squares is compiled. The resulting information, including work by Carolyn Francis and Claire Cooper Marcus, Cliff Moughtin, Leon Krier, and Camillo Sitte, is then critiqued and synthesized in order to establish function, form and spatial organization typologies of squares. These typologies address not only the use and formal attributes of individual squares, but also where squares should be located and how they can link to one another in order to form larger networks. Together, the research and types substantiate the square as both a refuge from the city and a place for community members to connect. In order to test the community connectivity of public squares, the research and typologies are applied to Super Neighborhood 22 in Houston, Texas. Houston established Super Neighborhoods as a means to link neighboring communities. In many cases, though, disconnections occur between the various natural and social systems found within the combined neighborhoods. Therefore, this Master’s Project and Report proposes a network of public squares as a means to unite the contrasting land uses, residents, and natural systems found within Super Neighborhood 22’s eleven smaller communities.
Keywords: square; piazza; Houston; Landscape Architecture (0390)